Conditioning of metal surfaces enhances Shewanella chilikensis adhesion. Issue 3 (16th March 2022) - Tuck, Benjamin; Watkin, Elizabeth; Somers, Anthony; Forsyth, Maria; Machuca, Laura L.
Abstract: Microbiologically influenced corrosion and biofouling of steels depend on the adsorption of a conditioning film and subsequent attachment of bacteria. Extracellular deoxyribonucleic acid (eDNA) and amino acids are biologically critical nutrient sources and are ubiquitous in marine environments. However, little is known about their role as conditioning film molecules in early biofilm formation on metallic surfaces. The present study evaluated the capacity for eDNA and amino acids to form a conditioning film on carbon steel (CS), and subsequently, the influence of these conditioning films on bacterial attachment using a marine bacterial strain. Conditioning films of eDNA or amino acids were formed on CS through physical adsorption. Biochemical and microscopic analysis of eDNA conditioning, amino acid conditioning and control CS surfaces demonstrated that organic conditioning surfaces promoted bacterial attachment. The results highlight the importance of conditioning the surface in initial bacterial attachment to steel.